Making Knowledge/Playing Culture: Theatre Festivals as Sites of Experiential Learning - Budde, Antje; Samur, Sebastian (Theatre Research in Canada / Recherches théâtrales au Canada)

(untitled) (Graduate Centre for the Study of Drama, University of Toronto, 2019)
(A project of the Digital Dramaturgy Lab at the Centre for Drama, Theatre and Performance Studies, University of Toronto) This article discusses the 2017 festival-based undergraduate course, “Theatre Criticism and Festival Dramaturgy in the Digital Age in the Context of Globalization—A Cultural-Comparative Approach” as a platform for experiential learning. The course, hosted by the University of Toronto’s Centre for Drama, Theatre and Performance Studies, and based on principles of our Digital Dramaturgy Lab, invited a small group of undergraduate students to critically investigate two festivals—the Toronto Fringe Festival and the Festival d’Avignon—in order to engage as festival observers in criticism and analysis of both individual performances and festival programming/event dramaturgy. We argue that site-specific modes of experiential learning employed in such a project can contribute in meaningful ways to, and expand, current discourses on festivalising/festivalization and eventification through undergraduate research. We focus on three modes of experiential learning: nomadic learning (learning on the move, digital mobility), embodied knowledge (learning through participation, experience, and feeling), and critical making (learning through a combination of critical thinking and physical making). The article begins with a brief practical and theoretical background to the course. It then examines historical conceptions of experiential learning in the performing arts, including theoriesadvanced by Burnet Hobgood, David Kolb and Ronald Fry, and Nancy Kindelan. The importance of the festival site is then discussed, followed by an examination of how the festivals supported thethree modes of experiential learning. Samples of student works are used to support this analysis.